MARRIAGE BETWEEN INDIVIDUALS OF THE SAME SEX, ACCORDING TO ISLAMIC LAW, POSITIVE LAW, AND HUMAN RIGHTS - Dicky Andrian (IAIN BONE, 2023)
This study examines the issue of same-sex marriage within the realms of Islamic law, positive law, and human rights. Existing literature reveals that both Islamic and positive laws tend to prohibit same-sex marriage or any form of LGBT relationships. However, human rights perspectives present a contrasting viewpoint. While Indonesia explicitly rejects same-sex marriage based on human rights, approximately 30 countries worldwide have legalized it, recognizing individual rights irrespective of sexual orientation. This research highlights the tensions between religious norms, positive law, and human rights principles regarding same-sex marriage, providing a foundation for further discussion on reconciling legal frameworks in an increasingly inclusive society that embraces sexual diversity.